2021
DOI: 10.36076/ppj.2021/24/e335
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Refracture following Primary Osteoporotic Vertebral Compression Fractures

Abstract: Background: In the aging population, osteoporosis and related complications have become a global public health problem. Osteoporotic vertebral compression fractures are among the most common type of osteoporotic fractures and patients are at risk of secondary vertebral compression fracture. Objectives: To identify risk factors for secondary vertebral compression fracture following primary osteoporotic vertebral compression fractures. Study Design: Retrospective study. Setting: Department of Orthopedic, an affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…NVCF after OVCF is common in clinical practice. According to previous reports, the incidence of NVCF after OVCF ranges from 9.3 to 38.4% (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Although the conclusions vary, most studies and systematic reviews have found no significant differences in the probability of NVCF between PVP and CT (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 98%
“…NVCF after OVCF is common in clinical practice. According to previous reports, the incidence of NVCF after OVCF ranges from 9.3 to 38.4% (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Although the conclusions vary, most studies and systematic reviews have found no significant differences in the probability of NVCF between PVP and CT (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Zhang et al found that older age, female sex, and smoking were risk factors for NVCF in patients with OVCF, whereas postoperative exercise and osteoporosis treatment were protective factors [ 19 ]. In addition, although not widely adopted, some studies have found a positive correlation between the HU values of CT and NVCF in patients with primary OVCF [ 14 , 20 , 21 ]. This study included 611 patients with OVCF.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying AVF are multifaceted, with some researchers proposing it as a natural progression of osteoporosis ( 21 ). Nevertheless, most studies suggest a strong association with osteoporosis and alterations in the local mechanical environment following the introduction of bone cement into the vertebra ( 22 - 25 ). Liu et al ( 22 ) and Movrin and Komadina ( 23 ) conducted analyses of AVF risk factors and discovered that lower vertebral BMD, intervertebral leakage, steroid use, excessive vertebral body restoration, and fractures located in the thoracolumbar region were all contributors to AVF.…”
Section: Discussionmentioning
confidence: 99%